(untitled) (Journal of Medicine, 2010)
A case of disseminated histoplasmosis in a 56-year-old apparently healthy male without any history of travel to endemic zone is described. The patient presented with fever with cough, respiratory distress and disorientation. Physical findings include fever, shortness of breath, reduced level of consciousness and hypotension. Diagnosis was confirmed by presence of Histoplasma capsulatum in bone marrow aspirate. This report illustrates the importance of recognizing the possibility of histoplasmosis in Bangladesh where mimickers of histoplasmosis like pulmonary tuberculosis and visceral leishmaniasis are extremely common. Keywords: Histoplasmosis, endemic mycoses, disseminated histoplasmosis, Histoplasma capsulatum, Bangladesh DOI:10.3329/jom.v11i1.4278 J Medicine 2010: 11: 70-73